Influence of Magnetic Field on Magnetic Properties of Electrodeposited Co-Ni-P Nanowires - Tu, Le Tuan; Thiem, Luu Van; Thang, Pham Duc (Communications in Physics, 2014)
The magnetic properties in Co-Ni-P nanowires arrays with diameter of 200 nm were investigated. All the samples were prepared by electrodeposition method with pH of 5.5 and at room temperature. During the deposition, a magnetic field in range of 0 - 750 Oe was applied parallel to the wires axis. The crystalline structure and morphology of the samples were characterized by X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM), respectively. The hysteresis loops were measured at room temperature using vibrating sample magnetometry (VSM). The mixture of hcp phases of the Co-Ni-P based nanowires has been indicated by the XRD pattern. The obtained results show that with 750 Oe magnetic field applied during deposition we can obtain maximum coercivity value (2180 Oe). The \(M_{r}/M_{s}\) ratio was rapid increased when the magnetic field changed from 0 Oe to 750 Oe.